Kualitas Pelayanan Publik Di Dinas Perpustakaan Umum dan Arsip Kota Malang: Layanan Perpustakaan Keliling - Rokhman, Arif Nur (Maliki Interdisciplinary Journal, 2024)
This study aims to evaluate the quality of mobile library services provided by the Public Library and Archives Office of Malang City. Data analysis reveals that the mobile library service has high-quality standards, as reflected in the high user satisfaction levels. Users expressed satisfaction with the availability of books, service accessibility, and the professionalism of the library staff. The findings align with previous studies that show mobile libraries effectively increase reading interest and expand literacy access in areas with limited stationary library services. Furthermore, this research contributes to the theory of mobile library services by proposing new variables such as operational flexibility and community involvement. The practical implications of this study include recommendations for the Malang City Library Office to enhance its services and provide policy references for the development of mobile library programs in other regions.